2019
DOI: 10.1039/c9ra06486a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profile analysis of Zhi-zi-chi decoction in feces of normal and chronic unpredictable mild stress-induced depression rats based on UHPLC-ESI-Q-TOF-MS/MS and multiple analytical strategies

Abstract: A total of 56 compounds from ZZCD were identified in feces of normal and depression rats. Then ten compounds were sieved as potential chemical markers that would reflect the antidepressant effect of ZZCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…A combination of HPLC and electrospray ionization MS/MS has been reported as a sensitive and rapid method for quantitative analyses (Keypour et al, 2010; Schuhmacher et al, 2008). UPLC–Q‐TOF–MS, a highly sensitive and specific method, also has been developed for identification of bioactive metabolites that were correlated with animal behaviors (K. Luo & Xing, 2019). Likewise, this method has been used to characterize the metabolic profile of hinokiflavone for the first time (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A combination of HPLC and electrospray ionization MS/MS has been reported as a sensitive and rapid method for quantitative analyses (Keypour et al, 2010; Schuhmacher et al, 2008). UPLC–Q‐TOF–MS, a highly sensitive and specific method, also has been developed for identification of bioactive metabolites that were correlated with animal behaviors (K. Luo & Xing, 2019). Likewise, this method has been used to characterize the metabolic profile of hinokiflavone for the first time (Chen et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Chol-8-en-24-oic acid, 7,15-dihydroxy-4,4,14-trimethyl-3,11-dioxo-, (5alpha)- et al, 2008). UPLC-Q-TOF-MS, a highly sensitive and specific method, also has been developed for identification of bioactive metabolites that were correlated with animal behaviors (K. Luo & Xing, 2019). Likewise, this method has been used to characterize the metabolic profile of hinokiflavone for the first time (Chen et al, 2019).…”
Section: Identification Of Ganoderma Lucidum From Three Originsmentioning
confidence: 99%
“…From day 2 of week 2, the stressors of CUMS were employed to exert stress on rats in CUMS, CUMS + ZZHPD, and CUMS + paroxetine hydrochloride (PX) groups for 8 weeks, and each rat was housed in each solitary cage. The forms of stressors were referred to our previous study [ 25 ], including water deprivation (24 hr), noise stress (1 hr), physical restraint (2 hr), forced swimming in ice-water (10 min), reversed light/dark cycle (24 hr), food deprivation (24 hr), clipping tail (5 min), cage tilting at 45°(24 hr), horizontal oscillation (20 min), and soiled bedding (300 mL water in 150 g sawdust bedding 20 hr). Rats in modeling groups including CUMS, CUMS + PX, and CUMS + ZZHPD were subjected to one or two styles of stressors randomly in a single day until day 7 of week 8.…”
Section: Methodsmentioning
confidence: 99%
“…For the assessment of the depression model and the antidepressant efficacy of positive medicine and ZZHPD, behavioral tests and biochemical analysis were employed. Referring to our previous study [ 25 ], the SPT, forced swimming test (FST), open-field test (OFT), and the concentration detection of 5-hydroxytryptamine (5-HT) in plasma were as follows: In simple terms, the ratio of 1% sucrose solution consumption and total liquid consumption (1% sucrose solution and pure water) of each rat in 1 h was regarded as the sucrose preference degree in SPT, the activity level of each rat in a black box without a top (80 × 80 × 40 cm) in 3 min was counted as the OFT score, and the immobility time of rats in a bucket filled with water in 4 min was recorded as the forced swimming test score. The enzyme-linked immunosorbent assay (ELISA) kits (mlbio, Shanghai, China) were used to detect the concentration of 5-HT in plasma.…”
Section: Methodsmentioning
confidence: 99%
“…Composed of dried ripe fruits of Gardenia jasminoides J. Ellis (genus Gardenia, family Rubiaceae, Fructus Gardeniae, Zhizi in Chinese, ZZ in brief) and fermented ripe seeds of Glycine max (L.) Merr. (genus Glycine, family Leguminosae, Semen sojae praeparatum, Dandouchi in Chinese, DDC in brief), Zhi-zi-chi decoction (ZZCD) is a typical TCM herb pair (ZZ is the monarch and DDC is the minister) chronicled in Shang Han Lun, which has been frequently utilized for treatment of depression, febrile diseases and agrypnia since approximate 202 AD in China (Yue et al, 2010) Studies have reported that iridoid glycosides and isoflavones are major active ingredients of ZZCD that showed various activities such as antiinflammation (Koo et al, 2006), antipyretic effect (Debnath et al, 2011) and anti-tumor effects (Hsu et al, 1997). Geniposide, one of the iridoid glycosides of ZZCD, exerts antidepressant effects on chronic unpredictable mild stress (CUMS)-induced depressive rats (Cai et al, 2015).…”
Section: Introductionmentioning
confidence: 99%